Working together when the problem is multi-faceted: understanding inter-agency working for the benefit of people with hoarding problems. (15th December 2022) - French, Sam G.; Lock, Karen; Zortea, Tiago; Hassall, Elaine; Bream, Victoria; Webb, Kathryn; Salkovskis, Paul M.
Abstract: Hoarding disorder is a surprisingly common problem which impacts on most areas of life. People who hoard typically have multiple agencies involved in their care due to the complex health and safety impact and risks associated with hoarding. 'Treatment' involves finding ways of supporting discarding large amounts, typically underpinned by CBT principles. We evaluated the impact and outcomes of a conference designed to boost professionals' confidence and understanding in working with hoarding problems, both individually and with other agencies with a view to improving inter-agency service provision. Changes in professionals' confidence and understanding were evaluated immediately before and after the conference. Conference participants' qualitative responses related to service improvements were analysed using content analysis. People with personal experience of hoarding issues subsequently participated in a focus group where the results of the conference were presented. These data were analysed using thematic analysis. Confidence and understanding in working with hoarding problems substantially increased from pre- to post-conference. Professionals identified a range of possible improvements, most commonly working more closely and improving communication with other agencies. People with personal experience suggested improvements across three over-arching themes: developing an improved understanding of hoarding, the need for improved resources, and improved multi-agency working. A multi-agency conference increased confidence and understanding in professionals working with hoarding problems, and improvements specified by both people with personal experience and professionals provide a useful guide to service improvement. Results provide a framework in which CBT approaches should be embedded. Key learning aims: (1) To assess the effectiveness of a multi-agency hoarding conference at improving understanding and confidence in working with hoarding problems. (2) To explore professionals' perceptions of improvements to multi-agency service provision. (3) To explore perceptions of improvements that could be made to multi-agency service provision from people with personal experience of hoarding problems.